Effects of Diffraction Propagation at 24GHz Spectrum Band - Femi-Jemilohun, Oladunni Juliet; D, Walker S. (Discoveries in Agriculture and Food Sciences, 2016)
The experimental measurement results of fast and slow signal fading due to corner diffraction characteristics of newly opened 100MHz bandwidths in the 24GHz spectrum for wireless communication is presented in this work. Two distinct regions are noticeable in the curve depicting these characteristics; a linear curve for the diffraction angles above 5 degrees, and a logarithmic curve for diffraction angles below 5 degrees. This feature being in agreement with what other research findings in similar working environment but at lower spectrum, as well as specifications by fundamental theory, points out the tremendous potential of this unlicensed 100MHz bandwidth for communication system for high and efficient delivery capacity especially in non-line of sight and obstructed transmission.